The Role of Creative Thinking and Entrepreneurial Motivation in Developing Innovative Behavior in Upcycled Denim Design in Vocational High School Students - Lathifaturrohmah, Lathifaturrohmah; Suhartini, Ratna; maspiyah, Maspiyah; Buditjahjanto, I Gusti Putu Asto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This research is motivated by the importance of innovative skills in vocational education, especially in sustainable fashion that demands creativity and an entrepreneurial spirit. The purpose of this study is to analyze the influence of creative thinking and entrepreneurial motivation on students' innovative behavior in designing outer upcycle denim at SMKN 6 Surabaya. The study used a quantitative approach with the SEM-PLS method. Instruments in the form of performance tests and questionnaires that have been tested for validity and reliability were given to grade XI Fashion Production Design students. The results showed that creative thinking and entrepreneurial motivation have a positive and significant effect on innovative behavior, with entrepreneurial motivation as the strongest influencing variable. Simultaneously, both variables explain 92.5% of the variation in students' innovative behavior. These findings emphasize the importance of strengthening creative thinking and entrepreneurial motivation in vocational education to produce innovative and independent graduates.